Integrins are enriched on aberrantly fucosylated tumour‐derived urinary extracellular vesicles. Issue 10 (10th October 2022) - Islam, Md. Khirul; Dhondt, Bert; Syed, Parvez; Khan, Misba; Gidwani, Kamlesh; Webber, Jason; Hendrix, An; Jenster, Guido; Lamminen, Tarja; Boström, Peter J.; Pettersson, Kim; Lamminmäki, Urpo; et al.
Abstract: Urinary extracellular vesicles (uEVs) are enriched with glycosylated proteins which have been extensively studied as putative biomarkers of urological cancers. Here, we characterized the glycosylation and integrin profile of EVs derived from urological cancer cell lines. We used fluorescent europium‐doped nanoparticles coated with lectins and antibodies to identify a biomarker combination consisting of integrin subunit alpha 3 (ITGA3) and fucose. In addition, we used the same cancer cell line‐derived EVs as analytical standards to assess the sensitivity of the ITGA3‐UEA assay. The clinical performance of the ITGA3‐UEA assay was analysed using urine samples of various urological pathologies including diagnostically challenging benign prostatic hyperplasia (BPH), prostate cancer (PCa) and bladder cancer (BlCa). The assay can significantly discriminate BlCa from all other patient groups: PCa (9.2‐fold; p = 0.00038), BPH (5.5‐fold; p = 0.004) and healthy individuals (and 23‐fold; p = 0.0001). Our results demonstrate that aberrantly fucosylated uEVs and integrin ITGA3 can be detected with fucose‐specific lectin UEA in a simple bioaffinity assay for the detection of BlCa directly from unprocessed urine.